Harboring data information security, law, and the corporation - Matwyshyn, Andrea M. (Stanford, Calif. : Stanford Law Books, 2009)
Engaged in a bottom-up investigation, this book reveals the emergent nature of data leakage and vulnerability, as well as some of the areas where our current regulatory frameworks fall short.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Data protection -- Law and legislation -- United States; Computer security -- Law and legislation -- United States; Business records -- Law and legislation -- United States; Law; United States of America, USA; Company law; Data protection law; Privacy & data protection